IMPACT OF AGRICULTURE ON SOIL POLLUTION IN BULGARIA - Harizanova-Bartos, Hristina; Stoyanova, Zornitsa (Economics of Agriculture, 2019)
This article proposes an interpretation of some statistical and empirical evidence of the impact of land pollution on agriculture and agriculture as pollutant. The new conditions concerning the quality of land and land pollution, together with the increasing demand for profitability of traditional agriculture, have led to problems of lack of sufficient farming lands and increased level of degraded soil quality. The land is characterized as a prime production factor in agriculture with own specifications and cadaster. The study emphasizes the contribution of the impact of agriculture on land usage in Bulgaria and the agriculture as affected by soil pollution. The parts of the article are as follows: 1) literature review concerning the connection of the agriculture as a soil/land pollutant and soil/land polluter; 2) Methodology is based on one-dimensional and twodimensional distribution of data collected by own survey. 3) According to the collected data is made analysis and some general conclusions which can be used as policy recommendations.